The influence of technological, social and contextual factors on continuous to use MOOCs among university students - Shabib Aldahmani, Salem Abdulla Saif (2022)
Human technology interaction has become the key driver for changes that improve society wellbeing and solve society problems. Due to the rapid growth of service sector, technology developers are targeting this sector, particularly profitable businesses. However, the social business, such as education has not received adequate attention. Even though E-learning and MOOCs application has the potential to enhance the capacity of educational institutions and boost up their quality, the efficiency of using these technologies is still questionable since the percentage of completion of MOOC courses is still very low. The literature suggests that technology motivation factors that influence users and educational quality as well as system are important to address this challenge. Even though, many studies investigated these factors, the problem still existed. Thus, this research aims to investigate technological and motivational factors that affect students’ continuous intention to use MOOCs. Both Technology Acceptance Model (TAM) and Technology Task Fit (TTF) theory were used to explain how students perceived the usefulness and ease of use of MOOCs, which influence their behavior to continuously use MOOCs. A questionnaire was randomly distributed to 315 students who use MOOCs in the Hamdan Bin Mohammed Smart University. Based on the analysis of data using Smart-PLS, the finding of this research confirmed that social motivation and technological factors are important determinants for perceived usefulness and ease of use. With respect to the contextual features of MOOCs, it was found that they significantly influence user’s perceived ease of use and usefulness of MOOCs. This research concluded that the users’ perceived usefulness and attitude have positive influence on students’ continuous to use MOOCs. It also contributes to the body of knowledge through the development of an integrative model that explains how to improve students’ continuance intention to use MOOCs by integrating social motivational and technological factors as well as MOOCs context features. The finding of this research provides a valuable guidance to educational institutions, especially the Arab region countries on how to improve the quality of their MOOCs’ services by providing a clear understanding of how to improve students’ continuance intention to use.